Oxygen consumption in fry and fingerling stages of Indian major carps analysed using indigenously developed respirometer - Mohapatra, B. C.; Das, L.; Mahanta, S. K.; Sahu, H.; Sahoo, P.; Lenka, S.; Anantharaja, K. (Indian Journal of Fisheries, 2017)
Experiments were conducted under laboratory conditions for determination of oxygen consumption of advanced fry, fingerlings and advanced fingerlings of Indian major carps, catla Catla catla (Hamilton, 1822); rohu Labeo rohita (Hamilton, 1822); and mrigal Cirrhinus mrigala (Hamilton, 1822) in freshwater medium of total alkalinity varying between 150-154 mg l-1, total hardness 130-140 mg l-1, pH 7.5-8.0, carbon dioxide 5.6-12.0 mg l-1 and temperature 31-35oC. Experiments were conducted in acrylic respirometers designed and developed for this purpose. The oxygen consumption values for advanced fry, fingerlings and advanced fingerlings of catla were 634±9, 565±27 and 516±28; rohu 549±26, 459±41 and 374±38 and mrigal 532±24, 449±28 and 343±30 mg kg body wt-1 h-1 respectively. In all stages, oxygen consumption values of catla varied significantly (p